CERITA RAKYAT DI KENAGARIAN SUNGAI NANIANG:KLASIFIKASI DAN FUNGSI - Rosna Marleni (Jurnal Elektronik WACANA ETNIK, 2010)
Folktale is one of media which record historical and cultural events. It’s also one form of local genius of the society. So, those folktales need to be documented for next generations. This article is result of documentation, classification, and function analysis of Nagari Sungai Naniang folktales. The research use folklore perspectives. The result shows there are seventeen story tales in Nagari Sungai Naniang. Twelve stories are classified into legend and five are tale. Furthermore, three stories serves as a projection of desire and expectation of society, one story serves as a validation tool and the institutions of a cultural system, eight story serves as an educational tool, and two stories serve as a supervisor of norms. Meanwhile, six of those folktales are in near extinct condition.